Exploring opportunities for sweetpotato in Nigeria - International Potato Center (2012)
For two months in late 2011, a rapid appraisal was conducted in selected states of Nigeria to understand the current role of sweetpotato in the food economy and to identify promising sweetpotato value chains for further research and investment. From the nutrition side, promotion of orange-fleshed sweetpotato linked to school feeding and other nutrition-linked endeavors appears promising. Fried sweetpotato products and the partial substitution of wheat flour with sweetpotato puree in bakery products are the best bets for income earning processed product investments.